The Distributional Impact of Taxes and Social Spending in Romania - Inchauste, Gabriela; Militaru, Eva (World Bank, Washington, DC, 2018)
The combined effect of taxes and social spending in Romania helps to reduce inequality, although less so than in other European Union countries. However, the combination of direct and indirect taxes and transfers leads to an increase in poverty, as direct cash transfers to poor households are not large enough to compensate them for the burden of indirect taxes. This is especially important for rural households and families with children. Moreover, recent reductions in the rates for personal income and value-added taxes are expected to have led to an increase in inequality, as most of the tax relief accrued to the top of the income distribution. Although these changes likely helped to reduce poverty, they were an expensive way to achieve a small decline in the poverty rate. Higher and better targeted social assistance spending could have achieved better distributional results at a much lower fiscal cost. These results call for greater use of simulation tools that could inform policy makers and the public of the fiscal costs and redistributive impacts of proposed reforms.